2015
DOI: 10.6061/clinics/2015(07)10
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the neutrophil to lymphocyte ratio in lung cancer: A meta-analysis

Abstract: Recently, a series of studies explored the correlation between the neutrophil to lymphocyte ratio and the prognosis of lung cancer. However, the current opinion regarding the prognostic role of the neutrophil to lymphocyte ratio in lung cancer is inconsistent.We performed a meta-analysis of published articles to investigate the prognostic value of the neutrophil to lymphocyte ratio in lung cancer. The hazard ratio (HR) and its 95% confidence interval (CI) were calculated.An elevated neutrophil to lymphocyte ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
122
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(137 citation statements)
references
References 36 publications
8
122
1
3
Order By: Relevance
“…The optimal cutoff values for NLR and PLR were determined using time-dependent receiver operating curve (ROC) analysis with survival ROC package (17). NLR and PLR cutoff points of 4.5 (11,12) and 258 (11) were used to stratify the patients, respectively. In terms of survival analyses, Kaplan-Meier method with log-rank test was used to analyze the correlation between variables and OS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimal cutoff values for NLR and PLR were determined using time-dependent receiver operating curve (ROC) analysis with survival ROC package (17). NLR and PLR cutoff points of 4.5 (11,12) and 258 (11) were used to stratify the patients, respectively. In terms of survival analyses, Kaplan-Meier method with log-rank test was used to analyze the correlation between variables and OS.…”
Section: Resultsmentioning
confidence: 99%
“…Whilst, the 7 th TNM classification stratifies the patients according to the extent of the primary tumor (T-stage), lymph node involvement (N-stage) and distant metastasis (M-stage) (6)(7)(8). However, the survival of the SCLC patients in the same stage varied dramatically, previous studies showed that various clinical factors of SCLC patients were predictive factors (9)(10)(11)(12). Unfortunately, the predictive value of these factors remained unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, a meta-analysis conducted by Yin Y and coll. reported that an elevated NLR predicted worse overall survival in lung cancer, with an adjusted HR of 1.2 in multivariate analysis (14). Similarly, in a narrative literature review, Faria SS and coll.…”
Section: Discussionmentioning
confidence: 87%
“…An imbalance of the immune system involving the NLR can be used as a biomarker for a systematic inflammatory response. In addition, it is used to predict the prognosis of patients with various cancers [10,11], cardiovascular diseases [12,13] and hemorrhagic stroke [14][15][16]. Recently, NLR was used to predict in-hospital mortality [17,18], 90-day mortality [19][20][21] and 90-day poor outcomes (mRS≥3) [4,[21][22][23] in patients with ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%